Histopathological Effects of Maternal Alcohol Consumption in the Pups of Albino Rats - R.S., Ebugosi; A.N., Okaka; A. U., Onochie; G.O., Chukwuma; P.O., Manafa; U., Ngenegbo; F.O., Chukwuezi; O.M., Chukwuma (European Scientific Journal, ESJ, 2017)
Alcohol consumption during pregnancy and lactation periods may result to some physical and histopathological changes in offsprings. This study was undertaken to investigate the possible effects of maternal alcohol intake on the testes and accessory sex organs of male pups of albino rats. Three groups of female albino rats; A, B and C were used for this study. Group A was the control group while groups B & C served as test groups. Eight male pups were randomly selected weekly (for five weeks) from each group and were sacrificed. The individual weights of the testes and accessory sex organs were determined and thereafter fixed in formol saline. Histopathological investigation was done and photomicrographs were taken. There was a significant reduction (P<0.05) in the mean weights of the testes in the test groups compared with control in all weeks under study. In contrast a significant reduction (P<0.05) in the mean values of the weights of ventral lobes of prostate and epididymis were only noticed in weeks 5 and 6 while the mean value of weights of the vas deferens showed significant reduction (P<0.05) in week 5 of the test groups compared with control group. The histopathological results revealed that exposure to alcohol caused focal coagulative necrosis of testicular seminiferous tubules in pre-natal alcohol exposed group B and a more diffuse coagulative necrosis of testicular seminiferous tubules in pre-and post- natal alcohol exposed group C. Therefore, there is the need for controlled alcohol consumption during pregnancy and lactation periods.